Total cholesterol and leptin concentrations are associated with prospective changes in systemic blood pressure in healthy pregnant women. - Farias, DR; Franco-Sena, AB; Rebelo, F; Schlüssel, M; Salles, G; Kac, G (2014)
BACKGROUND: Lipids and leptin have been associated with high blood pressure (BP) levels during pregnancy. The aim was to evaluate the associations between serum lipids and leptin concentrations during the first trimester and longitudinal changes of SBP and DBP in healthy pregnancies. METHODS: Prospective cohort of pregnant women followed at a public healthcare center in Rio de Janeiro, Brazil. SBP and DBP were obtained at the ≤13th, 20-26th, and 30-36th weeks of gestation and were the dependent variables. Serum lipids and plasma leptin concentrations were collected at 13 weeks or less of gestation and were the main independent variables. Statistical analyses included longitudinal linear mixed-effects regression models, with (β) coefficients and their 95% confidence intervals (CI). RESULTS: Mean BPs were 109.8/66.9, 107.8/64.3, and 111.2/66.9  mmHg, respectively in the 1st, 2nd, and 3rd trimester. Multiple longitudinal regressions revealed that leisure time physical activity before pregnancy (β(SBP) = -3.003, 95% CI = -5.034 to -0.971; β(DBP) = -2.620, 95% CI = -4.177 to -1.064), baseline BMI (β(SBP) = 4.003, 95% CI = 1.924-6.081; β(DBP) = 1.862, 95% CI = 0.252-3.412), parity (β(SBP) = -2.778, 95% CI = -4.627 to -0.929; β(DBP) = -1.780, 95% CI = -3.168 to -0.392), and Homeostasis model of assessment-Insulin Resistance (HOMA-IR; β(SBP) = 2.554, 95% CI = 0.552-4.557; β(DBP) = 2.962, 95% CI = 1.436-4.489) were the covariates independently associated with SBP and DBP changes. Monthly per-capita family income (β(SBP) = -0.006, 95% CI = -0.010 to -0.001), total cholesterol (β(SBP) = 2.094, 95% CI = 0.223-3.965), and leptin (β(SBP) = 2.211, 95% CI = 0.159-4.263) were associated only with SBP changes. CONCLUSION: Serum total cholesterol and leptin concentrations, HOMA-IR, and BMI were positively associated with changes in BP during healthy pregnancies, whereas physical activity, parity, and family income were negatively associated.